ANALISIS RENDAHNYA PEMAHAMAN MEMBACA CERITA ANAK PADA MATA PELAJARAN BAHASA INDONESIA SISWA KELAS V SD - Azahra, Azizah; Diba Catur Putri, Fara; Farhana, Husna; Amelia, Decenni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading comprehension is a fundamental skill that elementary school students must master to support their success in various subjects. However, many students still experience difficulties in comprehending reading material, particularly children's stories. This study aims to analyze the factors contributing to low reading comprehension in fifth-grade students and identify common errors. The study used a descriptive qualitative approach through observations, reading comprehension tests, and interviews with class teachers. The results indicate that low reading comprehension is influenced by low interest in reading, a lack of reading habits at home, the use of teacher-centered learning methods, and a lack of variety in reading media. Furthermore, students often make errors in identifying the main idea, summarizing the content of the text, and identifying characters and plot. These findings provide recommendations for improving reading comprehension through more interactive learning, the use of engaging children's stories, and the continuous development of reading habits.